Prevalence of SARS-CoV-2 in six districts in Zambia in July, 2020: a cross-sectional cluster sample survey - Lloyd B Mulenga, PhD; Jonas Z Hines, MD; Sombo Fwoloshi, MMed; Lameck Chirwa, MPH; Mpanji Siwingwa, MPH; Samuel Yingst, PhD; Adam Wolkon, MPH; Danielle T Barradas, PhD; Jennifer Favaloro, MS; James E Zulu, MBChB; Dabwitso Banda, MBChB; Kotey I Nikoi, BSc; et al. (Elsevier, 2021)
Summary: Background: Between March and December, 2020, more than 20 000 laboratory-confirmed cases of SARS-CoV-2 infection were reported in Zambia. However, the number of SARS-CoV-2 infections is likely to be higher than the confirmed case counts because many infected people have mild or no symptoms, and limitations exist with regard to testing capacity and surveillance systems in Zambia. We aimed to estimate SARS-CoV-2 prevalence in six districts of Zambia in July, 2020, using a population-based household survey. Methods: Between July 4 and July 27, 2020, we did a cross-sectional cluster-sample survey of households in six districts of Zambia. Within each district, 16 standardised enumeration areas were randomly selected as primary sampling units using probability proportional to size. 20 households from each standardised enumeration area were selected using simple random sampling. All members of selected households were eligible to participate. Consenting participants completed a questionnaire and were tested for SARS-CoV-2 infection using real-time PCR (rtPCR) and anti-SARS-CoV-2 antibodies using ELISA. Prevalence estimates, adjusted for the survey design, were calculated for each diagnostic test separately, and combined. We applied the prevalence estimates to census population projections for each district to derive the estimated number of SARS-CoV-2 infections. Findings: Overall, 4258 people from 1866 households participated in the study. The median age of participants was 18·2 years (IQR 7·7-31·4) and 50·6% of participants were female. SARS-CoV-2 prevalence for the combined measure was 10·6% (95% CI 7·3-13·9). The rtPCR-positive prevalence was 7·6% (4·7-10·6) and ELISA-positive prevalence was 2·1% (1·1-3·1). An estimated 454 708 SARS-CoV-2 infections (95% CI 312 705-596 713) occurred in the six districts between March and July, 2020, compared with 4917 laboratory-confirmed cases reported in official statistics from the Zambia National Public Health Institute. Interpretation: The estimated number of SARS-CoV-2 infections was much higher than the number of reported cases in six districts in Zambia. The high rtPCR-positive SARS-CoV-2 prevalence was consistent with observed community transmission during the study period. The low ELISA-positive SARS-CoV-2 prevalence might be associated with mitigation measures instituted after initial cases were reported in March, 2020. Zambia should monitor patterns of SARS-CoV-2 prevalence and promote measures that can reduce transmission. Funding: US Centers for Disease Control and Prevention.